Naphthyl or pyrenyl substituted 2-phenylcarbazoles as hole transporting materials for organic light-emitting diodes. (January 2017) - Chang, Chih-Hao; Krucaite, Gintare; Lo, Dain; Chen, Yun-Lan; Su, Chu-Chun; Lin, Tzu-Chun; Grazulevicius, Juozas Vidas; Peciulyte, Laura; Grigalevicius, Saulius
Abstract: A new series of 9-hexylcarbazole-based hole transporting materials (HTM) with naphthyl or pyrenyl substitutions were synthesized and characterized. The respective glass transition temperatures of the new HTM were estimated to be 58 and 61 °C, which can provide morphologically-stable films for electroluminescence (EL) applications. The pyrenyl substituted analogue possesses an adequate ionization potential and triplet energy gap of 5.54 eV and 2.48 eV, respectively, which makes it a suitable HTM for use in red phosphorescent organic light-emitting diodes (OLEDs). In contrast, the ionization potential of the naphthyl substituted analogues was estimated to be 5.72 eV, thus the p-type conducting dopant should be introduced for device fabrication. The respective peak efficiencies of the naphthyl and pyrenyl based OLEDs with the p-type dopant were recorded at 15.4% (26.0 cd/A and 24.2 lm/W) and 17.3% (26.1 cd/A and 19.1 lm/W), demonstrating their high potential for EL applications. Graphical abstract: Highlights: 9-Hexylcarbazole-based HTM with naphthyl or pyrenyl substitutions were synthesized. The hexylcarbazole-based HTMs possess adequate ionization potentials. The hexylcarbazole-based HTMs are appropriate host materials for p-type dopants. Red PhOLEDs using the 9-hexylcarbazole derivatives as HTMs.